Flavonoid extraction from Alpinia zerumbet (Pers.) Burtt et Smith leaves using different techniques and solvents - Victório, Cristiane Pimentel; Lage, Celso Luiz Salgueiro; Kuster, Ricardo Machado (Eclética Química, 2009)
The current study aims to verify the best method for a rapid and efficient extraction of flavonoids from Alpinia zerumbet. Dried leaves were extracted using distillated water and ethanol 70% by extraction methods of shaking maceration, ultrasonic, microwave and stirring. By the application of TLC and reversedphase HPLC techniques the rutin and kaempferol-3-O-glucuronide were detected. Ethanol 70% was more efficient for flavonoids extraction than water. No significant yielding variation was verified for ultrasonic, microwave and stirring methods using ethanol 70% (11 to 14%). The relative concentration of rutin and kaempferol-3-O-glucuronide, respectively, was higher by ultrasonic (1.5 and 5.62 mg g-1 dried leaves, respectively) and by microwave (1.0 and 6.64 mg g-1 dried leaves) methods using ethanol. Rapid and simplified extraction proceeding optimize phytochemical work and acquisition of secondary metabolites.